Representation of religions of African influence in CDD: A critical analysis of Umbanda in Brazil - Da Silva, Marcio Ferreira [UNESP]; De Almeida, Carlos Cândido [UNESP] (My University, 2018)
The representation of the Brazilian Umbanda religion is discussed from the point of view of the Theory of Social Representations. It is considered that Universal Classification Systems, such as the CDD, do not adequately represent this religion because its complexity is not welcomed by the system. Because of this, it can reinforce inequalities, religious intolerance and, above all, structural racism due to a misrepresentation that precludes access to knowledge on Umbanda.
Representacao das religioes de matriz africana na CDD: Uma analise critica da Umbanda no Brasil
Keywords: Afro-brazilian identity; Brazil; Classification systems; Dewey decimal classification; Knowledge organization; Representation of black people; Umbanda